2017
DOI: 10.2139/ssrn.3009203
|View full text |Cite
|
Sign up to set email alerts
|

The European Electronic Communications Code: A Critical Appraisal with a Focus on Incentivizing Investment in next Generation Broadband Networks

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A similar concern is found in the abovementioned paper by Briglauer et al (2017), where it is formulated in a softer manner stating that the outcome of an enhanced emphasis on co-investment and symmetric regulation is uncertain and depends on how it will be implemented. As it is expressed in the 8 statements in the theory section of the present paper, the correlations are not obvious.…”
Section: Correlation Analysismentioning
confidence: 55%
See 2 more Smart Citations
“…A similar concern is found in the abovementioned paper by Briglauer et al (2017), where it is formulated in a softer manner stating that the outcome of an enhanced emphasis on co-investment and symmetric regulation is uncertain and depends on how it will be implemented. As it is expressed in the 8 statements in the theory section of the present paper, the correlations are not obvious.…”
Section: Correlation Analysismentioning
confidence: 55%
“…The question raised by different observers (e.g. Briglauer et al (2017) and Serentschy ( 2018)) is whether the new regulatory framework will achieve this in reality. With the many different interests of stakeholders that have had to be taken into consideration, the question is whether the Communications Code has become incoherent and points in too many different directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telecom investment of networks construction is important in optimizing the performance and improving the quality of the networks. Briglauer [33] and Houngbonon [34] found that INVESTMENT has a positive effect on SUPPLY. Thus, this hypothesis is introduced to our conceptual model.…”
Section: Conceptual Model and Research Hypothesesmentioning
confidence: 99%